Direction matters: the unexpected role of azimuth in the spatial distribution of regeneration of Abies hickelii (Flous & Gaussen) - Hernández-Cruz, Iván (2025)
Understanding how individuals are spatially distributed in the early stages of their growth is crucial for comprehending the processes that shape the dynamics, structure, and size of populations, especially for those classified as at risk of conservation concern. The main objective of this study was to answer the question of whether the abundance of the natural regeneration of Abies hickelii (Flous & Gaussen) is associated with a specific direction, measured in relation to magnetic north, assuming that the mother tree is located in the center of high seed density. The hypothesis of equal proportions in the quadrants (north, south, east, and west) with respect to the reference trees was verified using 95% confidence intervals. Certain topographic attributes were analyzed using the Weibull function. Among the results, it was found that, regardless of altitude, slope, or slope orientation, natural regeneration is not uniformly distributed around the reference trees. On the other hand, when considering slope exposure, a significantly higher concentration of regeneration was observed on land exposed to the northeast (69%), while the remaining 31% was distributed across land oriented to the north, east, and south. These patterns emphasize the distinctive characteristics of threatened species, whose relevance is accentuated in the context of climate change, which influences the dynamics of natural regeneration. Furthermore, identifying areas with favorable exposures, such as those oriented to the northeast, can guide reforestation and protected area management projects to maximize the survival and growth of new individuals.